Removal of Heavy Metal from Industrial Wastewater Using Ultrasonic Assisted By Tea Waste As Adsorbent - Mohd Ariff, Kamali (2010)
Wastewater from industry can lead to water pollution if untreated, especially due to its high concentration of heavy metals. Heavy metals are considered extremely harmful because they can cause illnesses, disorder and diseases to human. Therefore, industrial wastewater containing heavy metal should be treated before discharge to the water stream but its treatment is very costly. There are several techniques to remove heavy metals from wastewater such as biosorption, filtration and adsorption of heavy metal but there is some limitation such as long treatment time. This research is about the efficiency of combination method between ultrasonic and adsorption process to remove zinc, Zn and nickel, Ni from fertilizer factory wastewater. The parameters analyzed in this research are amounts of adsorbent in solutions from 0.5 g to 2.9 g of tea waste, different ultrasonic temperature from 40° C to 80° C and different sonication time from 5 minute to 29 minutes. After several experiment and analysis of results, it is found that the optimum condition to remove Zn and Ni from 100 ml wastewater is at 24 minute sonication time and 75°C ultrasonic temperature for 2.5 g amount of adsorbent which can remove about 79% of zinc and 71% of nickel. According to the result, the method of ultrasonic assisted by adsorption process to remove heavy metal from industrial wastewater can be use effectively because it can reduce energy, time and cost of treatment.